Using Animaker Application to Enhance Students' Motivation on Learning English Parts of Speech (Wahana Didaktika : Jurnal Ilmu Kependidikan, 2023)
The aim of this study is to investigate wheter Animaker Aplication can enhance students’ motivation on learning English parts of speech. The method used in this research is pre experimental design. The sample of this research are 30 students of the third semester of management study program Faculty of Economy and Business University of PGRI Palembang. In collecting the data, the writer used  questionnaire sheets  and direct observation. The questionnaire is used before and after the treatment which  consist 10 statements with likert scale scoring.  To  analyze the data  the writer used percentage analysis related to every single statement in the questionare. Based on the data analyzed and the finding it shows that the use Animaker application in teaching and learning parts of speech can enhance students learning motivation.